SOME REMARKS ON LANDAU–GINZBURG POTENTIALS FOR ODD-DIMENSIONAL QUADRICS. (18th December 2014) - GORBOUNOV, VASSILY; SMIRNOV, MAXIM
Abstract: We study the possibility of constructing a Frobenius manifold for the standard Landau–Ginzburg model of odd-dimensional quadrics Q 2 n +1 and matching it with the Frobenius manifold attached to the quantum cohomology of these quadrics. Namely, we show that the initial conditions of the quantum cohomology Frobenius manifold of the quadric can be obtained from the suitably modified standard Landau–Ginzburg model.